The Effect of Dividend Policy on Company Value with Profitability as an Intervening Variable in LQ45 Companies Listed on the Indonesia Stock Exchange - Tika Pramana; Mohamad Adam; Marlina Widiyanti; Isnurhadi Isnurhadi (Publikasi Indonesia, 2024)
This study aims to analyze the influence of dividend policy on the value of companies with profitability as an intervening variable in companies that are members of LQ45 listed on the Indonesia Stock Exchange (IDX). LQ45 is a stock index consisting of 45 selected companies with high liquidity and large market capitalization. A dividend policy is a company's decision to distribute profits to shareholders, which can affect the market's perception of the company's value. Profitability is measured using Return on Assets (ROA), which reflects a company's ability to generate profits from the assets it owns. This study uses a quantitative approach with secondary data taken from the annual financial statements of LQ45 companies during the 2019-2022 period. Data analysis was carried out using multiple regression methods to test the relationship between dividend policy, profitability, and company value. The results of the study show that the dividend policy has a significant positive influence on the company's value, both directly and through profitability as an intervening variable. This finding has implications for company management in designing optimal dividend policies to increase company value, as well as for investors in considering dividend policies and profitability as important factors in making investment decisions.